Introduction. Issue 4 (2nd October 2019) - Baraitser, Lisa
ABSTRACT: In 2017, Noreen Giffney and Eve Watson brought out a landmark edited collection entitled Clinical Encounters in Sexuality: Psychoanalytic Practice & Queer Theory with the open-access, nonprofit publisher Punctum Books. This issue of Studies in Gender and Sexuality gathers a range of responses from scholars and clinicians to the book. To introduce the issue, I offer some thoughts, inspired by Bion, on "encounter."